STRATEGI PEMANFAATAN MEDIA YOUTUBE OLEH NET TV SUL-SEL (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This thesis aims to find out how the Strategy for Utilizing YouTube Media by Net TV Sul-Sel and utilizing YouTube media to compete with other local media in Makassar in getting the audience market.The type of research used is descriptive qualitative, namely, researchers directly obtaining information from informants such as circumstances, processes, events, or events and others stated in the form of statements. The source of data in this study is the editor of NET TV Sul Sel, and also a spectator who often accesses it. The data collection method used is field research through observation, interviews, and documentation.The results of this study indicate that the Strategy for Utilizing YouTube Media by Net TV Sul-Sel, namely: First, the steps to get viewers interested in watching video shows on Youtube, namely: Selection of thumbnails, selection of interesting titles, interesting content, and sharing to the media other social. The two obstacles experienced by NET TV Sul Sel in the use of YouTube media are performance disturbances due to slow internet network connections, YouTube servers having problems from time to time, and being unable to reach areas where internet connections do not yet exist. The three opportunities for NET TV Sul Sel in utilizing YouTube media are: through endorsement, AdSense, advertising content, trading/business, and guest stars/speakers/presenters.